Bereaved Families: A Qualitative Study of Therapeutic Intervention - Moriconi, Valeria; Cantero-García, María (Frontiers in Psychology, 2022)
Background A child’s death is the most stressful event and the most complex grief that families face. The process of psychological adaptation to the illness and death of a child is difficult due to a variety of emotional reactions. Parental grief had received the attention of researchers only in recent years when it became clear that this reality differs substantially from the general grief process. Objective This work aims to highlight the needs of bereaved parents; increase the specificity and effectiveness of the therapeutic approach to prevent complications in the process of loss-making; and find the recurrent thematic nuclei in the development of bereavement present in a therapeutic group of parents who have lost their child to an onco-hematological disease. Method Between 2011 and 2016, five therapeutic groups for the grief elaboration were made. The sample included a total of 50 parents of children who died from cancer between the ages of 0 and 21 years. Content analysis was carried out as a qualitative analysis method. The SAS® Text Miner software (SAS Institute Inc, 2004) was used to read, interpret, classify and integrate the data from numerous sources. Results The development and consecutive interpretation of the 5 clusters have been carried out to analyze the related topics using the node “Topic Analysis” and requesting the subdivision into five topics. Four topics have been well defined. Clear topics are reducible to categories of emotional relief, tools, legacy, and unfinished business. The topic analysis provides interesting indications about the different interpretive journeys of the bereavement situation and offers ideas regarding the different types of social responses. Conclusions After reviewing the existing bibliography, we have confirmed the lack of specific literature on the problem of grief in parents whose children have died from cancer. Much research has shown that parents who lose a child to cancer want support, and there are still few studies on the most effective interventions for this group.